ВТРАТИ, НАГРІВ У КРИШКАХ БАКІВ ПОТУЖНИХ ТРАСФОРМ - Басова , А.В.; Іванков , В.Ф.; Хімюк , І.В. (Інститут електродинаміки НАН України, Київ, 2013)
The main approaches to analytical estimations and three-dimensional modeling by finite element method of electromagnetic and thermal processes in the tank covers using ANSYS software are presented. The results of an investigation of three-dimensional constructions of tank covers of three-phase transformers taking into account not only the magnetic fields in taps, but also the leakage fields in windings, are provided. Referances 6, figures 16.